Dialysis modality choice in elderly patients with end-stage renal disease: a narrative review of the available evidence. Issue 1 (15th December 2015) - Segall, Liviu; Nistor, Ionuţ; Van Biesen, Wim; Brown, Edwina A.; Heaf, James G.; Lindley, Elizabeth; Farrington, Ken; Covic, Adrian
Abstract : The number of elderly patients on maintenance dialysis has rapidly increased in the past few decades, particularly in developed countries, imposing a growing burden on dialysis centres. Hence, many nephrologists and healthcare authorities feel that greater emphasis should be placed on the promotion of home dialysis therapies such as peritoneal dialysis (PD) and home haemodialysis (HD). There is currently no general consensus as to the best dialysis modality for elderly patients with end-stage renal disease. In-centre HD is predominant in most countries, although it is widely recognized that PD has several advantages over HD, including the lack of need for vascular access, continuous slow ultrafiltration, less interference with patients' lifestyle and lower costs. Comparisons of outcomes between elderly patients on PD and HD rely on observational studies, as randomized controlled trials are lacking. The results of these studies are variable. However, most of them suggest that survival rates are largely similar between the two modalities, except for elderly patients with diabetes and/or beyond 1–3 years from dialysis initiation, in which cases HD appears to be superior. An equally important aspect to consider when choosing dialysis modality, particularly in this age group, is the quality of life, and in this regard most studies found no significant differences between PD and HD. In these circumstances, we believe that dialysis modality selection should be guided by patient's preference, based on comprehensive and unbiased information. A multidisciplinary team should review elderly patients starting on dialysis, aiming to identify possible barriers to PD and home HD, including physical, visual, cognitive, psychological and social problems, and to overcome such barriers by adequate care, education, psychological counselling and dialysis assistance.